Communicating the User Experience : a Practical Guide For Creating Useful UX Documentation - Cable, Steve; Cable, Steve (Wiley, 2011)
A clear and focused guide to creating useful user experience documentation As web sites and applications become richer and more complex, the user experience (UX) becomes critical to their success. This indispensable and full-color book provides practical guidance on this growing field and shares valuable UX advice that you can put into practice immediately on your own projects. The authors examine why UX is gaining so much interest from web designers, graduates, and career changers and looks at the new UX tools and ideas that can help you do your job better. In addition, you'll benefit from th.